The Payment for Environmental Services in Costa Rica - González Ballar, Rafael (Universidad de Costa Rica - Colegio de Abogados y Abogadas de Costa Rica, 2014)
The payment of environmental services (PES) in Costa Rica has become a really important and novel issue which must be conceived as an economic instrument and a financial order system that tries to repay the land owners under the forest regime for the environmental benefits they provide to the country, in an effort to conserve and sustain the usage of primary and tropical forests. Amongst the benefits of such efforts are the reduction of the gases that cause global warming (through carbon fixation and its storage, avoiding the excess accumulation of CO2 in the atmosphere) and the protection of biodiversity. At the local and national level the protection of water for human consumption and hydroelectric generation, as well as for landscape and scenic preservation are also very important. However, we have found some problems with the command and control options of Costa Rica's economical instruments (no political consensus, weak administrative agencies, no financial sustainability and no control of the process).